“Autobiographical in Feeling But Not in Fact”: the Finale of Alice Munro’s Dear Life - Ładuniuk, Magdalena (Studia Anglica Posnaniensia, 2016)
This article discusses “The Eye,” “Night,” “Voices” and “Dear Life” in relation to Munro’s biography. It reflects on the narrative techniques the author uses to create the impression of authenticity and autobiographicality in the stories. It also aims to answer the question whether they should be indeed classified as Munro’s autobiography.